The effects of brief individual cognitive behavioural therapy for depression and homesickness among international students in Malaysia - Saravanan, Coumaravelou; Alias, Alizi; Mohamad, Mardiana (Elsevier BV, 2017)
Background Students who go to other countries for higher education face various psychological problems, particularly homesickness and depression. The objectives of this study were to: (a) identify differences between students who did and did not receive brief individual cognitive behavioural therapy (CBT) for depression to reduce homesickness; (b) identify whether brief individual CBT for depression reduces the level of homesickness in students between pre-, post- and follow-up assessment; and (c) compare the scores of students experiencing only homesickness and those experiencing both homesickness and depression. Method The sample consisted of 520 first-year undergraduate international students. The experimental group contained students who were diagnosed with depression and homesickness and received seven sessions of brief individual CBT for depression to reduce homesickness. The control group contained students who were diagnosed with depression and homesickness and received one session of advice and suggestions. The comparison group contained students who experienced only homesickness and did not receive any interventions. The study used the comparison group to determine if an interaction effect existed between students experiencing only homesickness and students experiencing both homesickness and depression. Results Students who received brief individual CBT displayed a significant reduction in their homesickness and depression scores compared to the scores of students in the control group. Students who experienced only homesickness exhibited a significant reduction in the scores on homesickness in the post-assessment compared to the control group's post-assessment homesickness scores. Limitation The results of this study cannot be generalized as data were collected from three universities in Malaysia. The follow-up assessment was conducted six months after the post-assessment, which also limits generalizability beyond six months. Conclusion Overall, homesickness is considered a normal reaction. Brief individual CBT for depression is effective in reducing homesickness and depression among international students.